Non-invasive, minute-to-minute estimates of systemic arterial pressure and pulse pressure variation using radial artery tonometry. (April 2013) - Colquhoun, Douglas A.; Forkin, Katherine T.; Dunn, Lauren K.; Bogdonoff, David L.; Durieux, Marcel E.; Thiele, Robert H.
Abstract The Tensys T-line uses tonometry to reproduce the arterial blood pressure tracing non-invasively. The purpose of this study was to assess the agreement between estimates of the T-line and an intra-arterial catheter (for both mean arterial pressure [MAP] and pulse pressure variation [PPV]) in the setting of spine surgery. Continuous blood pressure data were collected for 7507 minutes from 25 patients. Five increasingly aggressive T-line filters were applied. The mean bias for mean, diastolic and systolic blood pressure ranged from 3.4–6.4, 3.1–7.1 and 0.1–0.8 mmHg and 6.5–11.8% for PPV. Ninety-five per cent confidence intervals for mean, diastolic and systolic blood pressure ranged from 24–28, 23.1–24.7 and 33.4–35.6 mmHg for 14–21% for PPV. The limits of agreement preclude the use of the T-line for reliable estimation of MAP or PPV in spine surgery.